Covalent Co-O-V and Sb-N Bonds Enable Polyoxovanadate Charge Control - Rasmussen, Maren; Naether, Christian; Van Leusen, Jan; Koegerler, Paul; Zhechkov, Lyuben; Heine, Thoma; Bensch, Wolfgang (Inorganic Chemistry, 2017)
The formation of [CoII(teta)2CoII2(tren)(teta)2VIV15SbIII6O42(H2O)]·ca.9H2O [teta = triethylenetetraamine; tren = tris(2-aminoethyl)amine] illustrates a strategy toward reducing the molecular charge of polyoxovanadates, a key challenge in their use as components in single-molecule electronics. Here, a V-O-Co bond to a binuclear Co2+-centered complex and a Sb-N bond to the terminal N atom of a teta ligand of a mononuclear Co2+ complex allow for full charge compensation of the archetypal molecular magnet [V15Sb6O42(H2O)]6-. Density functional theory based electron localization function analysis demonstrates that the Sb-N bond has an electron density similar to that of a Sb-O bond. Magnetic exchange coupling between the VIV and CoII spin centers mediated via the Sb-N bridge is comparably weakly antiferromagnetic.
CRIS-Team Scopus Importer:2022-04-14